PENDAMPINGAN DALAM PELESTARIAN PERMAINAN TRADISIONAL KETAPEL UNTUK MENDORONG TRANSFORMASI SOSIAL DI KELURAHAN RAWA MAKMUR - Muhammad Khairul Rijal (P3M STAI Sangatta, 2025)
The traditional slingshot game (katapel) is a part of local culture that is increasingly marginalized due to rapid technological development. This community service activity aimed to preserve the katapel game in Rawa Makmur Sub-district, Palaran District, through a participatory, community-based approach. Students from the Community Service Program (KKN) of Sultan Aji Muhammad Idris State Islamic University (UINSI) Samarinda acted as facilitators in regular training sessions organized by local residents. The strategies involved mentoring, activity documentation, and cultural awareness dissemination. The results showed increased participation among children and youth, along with a growing collective awareness to preserve traditional games. The katapel serves not only as entertainment but also as an educational tool that fosters motor skills, discipline, and social interaction. Preserving traditional games is an important step toward building character and strengthening local cultural identity amid modernization.